A Critical Muslim Perspective on Liberal Democracy: Malek Bennabi, Social Justice and Religious Ethics - Belhaj, Abdessamad (Journal of Islamic and Social Studies, 2025)
Malek Bennabi (1905–1973), a well-known Muslim reformist from Algeria, offered one of the most thoughtful and rational criticisms of liberal democracy within the broad framework of Muslim political theory. At the same time, he supported the political freedom that liberal democracy fostered. Bennabi identified three problems with liberal democracy. First, the theory and the reality of freedom diverge because liberal democracies both offer and deny their citizens the freedom that is guaranteed by constitutions and human rights declarations. Second, large private interest groups benefit from liberal democracies at the expense of the majority of citizens. Third, liberal democracies are vulnerable to class conflict as the divide widens between political and social principles leading to revolutions or coups that bring about socialist governments which reduce political freedoms. This article discusses Bennabi's views on Islam and democracy, including his criticism of liberal democracy for lacking social security and his view of democracy as freedom of choice and from want.